2011
DOI: 10.1007/s12491-011-0008-0
|View full text |Cite
|
Sign up to set email alerts
|

Fysiotherapie voor volwassen patiënten met critical illness

Abstract: Samenvattingx x x De Task Force heeft de beschikbare literatuur over de effectiviteit van fysiotherapie bij volwassen patiënten met acute en chronische critical illness. Bewijs uit gerandomiseerde gecontroleerde onderzoeken of meta-analyses is beperkt en de meeste aanbevelingen waren van niveau C (bewijs uit niet-gecontroleerde of niet-gerandomiseerde onderzoeken, of uit observatieonderzoeken) en D (deskundig oordeel). Niettemin werden de volgende problemen als evidence-based doelen voor fysiotherapie vastgest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…27 Though it seems that early physical training should be helpful in mechanically ventilated patients who are confined to bed, no clear evidence has yet emerged in the literature in favor of early physical training in patients in the ICU setting. 9 A randomized trial in a medical ICU found that only 13% of patients ventilated for Յ 72 hours were eligible for interrupting sedation and participating in whole-body rehabilitation to recover their basic activities. 11 The feasibility of an early training program in the ICU to improve BADL functioning at hospital discharge was been further confirmed in medical and surgical mechanically ventilated patients, 10 even during an episode of acute respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Though it seems that early physical training should be helpful in mechanically ventilated patients who are confined to bed, no clear evidence has yet emerged in the literature in favor of early physical training in patients in the ICU setting. 9 A randomized trial in a medical ICU found that only 13% of patients ventilated for Յ 72 hours were eligible for interrupting sedation and participating in whole-body rehabilitation to recover their basic activities. 11 The feasibility of an early training program in the ICU to improve BADL functioning at hospital discharge was been further confirmed in medical and surgical mechanically ventilated patients, 10 even during an episode of acute respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded patients with persistent altered sensorium, major cardiac arrhythmia, 9 history of underlying neuromuscular disease or acquired polyneuromyopathies, unable to perform physical training due to preexisting joint dysfunction, or with conditions that could have negatively influence the prognosis. We used electromyography to assess for acquired ICU neuropathy and myopathy (Fig.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate diagnosis of respiratory conditions is of paramount importance to physiotherapists 51 to enhance treatment selection and monitor treatment effectiveness [6]. TUS may provide an 52 alternative, and more accurate, imaging option for physiotherapists that can be performed at 53 the bedside and in real-time.…”
Section: Introduction 45mentioning
confidence: 99%
“…16,19 A força-tarefa da European Respiratory Society and Europen Societyof Intensive Care Medicine, em 2008, e o Departamento de Fisioterapia da Associação de Medicina Intensiva Brasileira, em 2012, descrevem uma hierarquia de atividades de mobilização na UTI seguindo uma sequência de exercícios que se iniciam a partir da mudança de decúbito, com grau de recomendação Nível B para mobilização precoce e ortostatismo. 16,20 Nossos resultados revelam que a sedestação (91,2%) foi a intervenção para MP mais citada pelos participantes. Segundo Hickmann et al 21 , quando acompanhada de exercícios ativos, otimiza a aeração pulmonar e minimiza a hipoxemia.…”
Section: Discussionunclassified